Organizations and the sustainability mosaic crafting long-term ecological and societal solutions - Sharma, Sanjay, 1955-; Starik, Mark, 1951-; Husted, Bryan, 1957-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2007)
The contributors to this book present research on crafting long-term ecological and societal solutions in order to achieve sustainability. The in-depth analyses explore the interactions among social, environmental, and development impacts of organizations at community, regional, national and global levels. In doing so they shed light on the way forward amidst the complexity of issues involved, referred to here as the sustainability mosaic.
1. Organizations and the sustainability mosaic : crafting long-term ecological and societal solutions / Bryan Husted, Sanjay Sharma and Mark Starik -- 2. Envisioning an ecologically sustainable society : an ideal type and an application / Gordon Rands ... [et al.] -- 3. A use-centered perspective on sustainability : a case-study of land use in the American Southwest / Christa Walck -- 4. Changing practice on sustainability : understanding and overcoming the organizational and psychological barriers to action / Andrew J. Hoffman and Max H. Bazerman -- 5. Institutionalization as a prerequisite for sustainable corporate development / Frank Wijen -- 6. Stakeholder salience, issues management and mapping new ways to sustainability / David Saiia -- 7. Stakeholder management and sustainability evaluation and reporting system (SERS) : a new corporate performance management framework / Francesco Perrini and Antonio Tencati -- 8. Who can act on sustainability issues? corporate capital and the configuration of organizational fields / Jennifer A. Howard-Grenville, Andrew J. Hoffman and C.B. Bhattacharya -- 9. The political-institutional dimension of socio-environmental strategies : the game of Aracruz Celulose S.A. versus Tupiniquim and Guarani Indians / Celio Andrade -- 10. Regulating business for sustainable development / Peter Utting -- 11. The professionalization of sustainability / Deborah Rigling Gallagher.
Includes bibliographical references and index.
Keywords: Sustainable development; Industries -- Social aspects; Environmental economics; Economic development -- Moral and ethical aspects; Social justice; Electronic books